PENGARUH MINAT BELAJAR, PERILAKU BELAJAR, KECERDASAN INTELEKTUAL DAN KECERDASAN EMOSIONAL TERHADAP TINGKAT PEMAHAMAN AKUNTANSI - Susi Susanti, Rispantyo & Djoko Kristianto (Universitas Slamet Riyadi, 2017)
This research aim to examine impact of learning behavior, IntellectualIntelligence, and emotional intelligence towards the level of understanding ofaccountancy student. This study used a survey method that uses primary datacollected from questionnaires. The population in this study were students at the endof the Faculty of Economics Department of Accounting at Surakarta. The numberof samples taken in this study are 75 students from STIE AUB Surakarta. Theresults showed that the partial intelligence and emotional intelligence significantlyinfluence the understanding of accounting whereas spiritual intelligence andlearning behavior has no Influence on the understanding of accounting.Keywords: interest to lear, learning behavior, Intellectual Intelligence, emotionalintelligence, level of accounting understanding